Program Proyek Kreatif dan Model Bisnis di SMKN 2 Dumai - Soni Fajar Mahmud; John Suarlin; Elisa Hafrida; Devit Satria (Journal Of Computer Science Contributions (JUCOSCO), 2025)
The development of the creative economy requires vocational education institutions to prepare students who possess not only technical competencies but also entrepreneurial skills and mindsets. However, learning products produced by vocational high school students are often limited to academic assignments and have not been optimally directed toward market-oriented business ideas. This community service program aims to foster entrepreneurial spirit among students of SMKN 2 Dumai through the implementation of Project-Based Learning (PjBL) integrated with the Business Model Canvas (BMC). The program was conducted on October 22, 2025, involving 25 students who were divided into six working groups. The implementation methods included the delivery of entrepreneurship and BMC materials, group formation, intensive mentoring in business model development, project presentations, and evaluation and reflection. Program evaluation was carried out using a BMC assessment rubric and pre- and post-activity questionnaires to measure students’ entrepreneurial understanding. The results showed that the level of achievement for non-financial BMC elements, such as customer segments, value propositions, and channels, reached 78%, while financial and partnership-related elements achieved 62%. These findings indicate that students more easily understand experiential and customer-oriented aspects compared to financial planning components. Overall, the program effectively improved students’ entrepreneurial understanding, creativity, and critical thinking skills. It can be concluded that integrating project-based learning with structured business modeling and evaluation plays an important role in preparing vocational students to face the challenges of entrepreneurship and the creative economy.